Strategi Pengembangan Life Skill Santri Melalui Kegiatan Muhadhoroh - Nuril Darmela Chaerunnisa; Daden Fikruzzaman (THORIQOTUNA: Jurnal Pendidikan Islam, 2025)
Islamic boarding schools are Islamic educational institutions that have grown and developed rapidly until now, but in the development phase, the condition of Islamic boarding schools is not far behind other general educational institutions. Even in the past, graduates from Islamic boarding schools were considered to have non-modern thinking and only knew Islamic education. Therefore, Islamic boarding schools are currently oriented towards developing life skills in order to transform their knowledge with the development of the times. Efforts to develop life skills in Islamic boarding schools to lead to the production of potential students require a mature development strategy, so that the output of Islamic boarding schools can be relied on and at least be able to recognize further the patterns developed in transforming any scientific modules in order to produce and empower abilities. In particular, traditional religious studies at the Suryalaya Islamic Boarding School develop the life skills of students through muhadharah activities to train public speaking skills in order to optimize individual potential. This study aims to identify strategies for developing students' life skills through muhadharah and evaluate the results of these strategies. The methodology used is qualitative descriptive research, with data collection through observation, documentation, and interviews with the head of the pengajian, muhadharah instructor, santri council administrators, and santri. The results of the study indicate that the strategy of developing life skills through muhadharah is quite successful and effective, indicated by the increase in the motivation of the santri. This activity includes good planning, namely by providing training, guidance, motivation, and awards. The results obtained include personal, social, academic and vocational skills. It can be suggested for further researchers to further investigate the strategy of developing santri's life skills through muhadhoroh activities at the Suryalaya Islamic Boarding School.